Mikroenkapsulasi Daun Pala Menggunakan Maltodekstrin dan Gom Arab dengan Teknik Spray Drying - Sabrina Dahlizar; Della Irsalina; Nelly Suryani; Ofa Suzanti Betha; Estu Mahanani Dhilasari; Sofa Fajriah; Maulina Handayani; Mutia Sari Wardana (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2026)
Nutmeg leaves (Myristica fragrans H.) are a rich source of various types of phenolic compounds that have exhibited a strong correlation with antioxidant capacity. The inherent instability of phenolic compounds poses significant challenges for their application in the pharmaceutical sector. Spray–drying microencapsulation has emerged as a promising strategy to overcome these challenges. The research aims to evaluate the physicochemical properties and the antioxidant activity of the spray-dried microcapsule of nutmeg leaves. There are variations in extract: encapsulant concentration, including FM-1 (1:2), FM-2 (1:3), and FM-3 (1:4), with a 1:1 encapsulant ratio between maltodextrin and gum arabic. The spray-dried nutmeg leaves were evaluated for morphology, particle size distribution, yield, moisture content, flowability, angle of repose, and encapsulation efficiency. Additionally, antioxidant activity tests were conducted using the DPPH method. The research showed that microcapsules of each formula have spherical and wrinkled shapes. The characteristics of the microcapsules for each formula yield 29.63%, 33.23%, and 33.85%, with moisture content of 7.31%, 9.32%, and 10.01%. The particle sizes measured were 4.58 μm, 5.55 μm, and 7.16 μm; flow rates were 0.59 g/s, 0.75 g/s, and 1.04 g/s; angles of repose were 41.71 °, 37.7 °, and 36.72 °, respectively (FM-1, FM-2, FM-3). The encapsulation efficiencies were 46.63%, 34.32%, 25.66%, respectively. The nutmeg leaves extract exhibited very strong antioxidant activity, with an IC50 value of 36.1 ppm. In contrast, the antioxidant activity of the microcapsules was relatively weak, with IC50 values of 239.07 ppm, 555.29 ppm, and 755.84 ppm, respectively (FM-1, FM-2, FM-3). This study showed that the spray-dried microcapsules of nutmeg leaves from the three formulas have morphologies, particle size distribution, angle of repose, and moisture content that met the requirements. However, the yield, flow rate, and encapsulation efficiency have not met the requirements.